Requirements analysis in the implementation of integrated PLM, ERP and CAD systems - Muni Prasad, Giddaluru; James, Gao; Raj, Bhatti; Satya, Shah (Cranfield University Press, 2013)
Product Lifecycle Management (PLM) system implementation is a major investment when the technology is used in manufacturing companies. This paper provides an analysis of the requirements for the integration of PLM systems with Enterprise Resource Planning (ERP) systems incorporating the design aspects of Computer Aided Design and Manufacturing (CAD/CAM) within the product development process. PLM implementation deals with various existing product data and information generated over years both from CAD and ERP systems. Data integration is very challenging and has important impact on future decisions while creating new processes. The information management plays very important role not only in PLM implementation but also in the way this will be used in future production. Therefore it is very important to analyse how product information is transferred to PLM system. It also need to be investigated that what, when and how the data will flow from and to PLM systems.
Keywords: Product Life Cycle Management (PLM); Computer Aided Design and Manufacturing (CAD/CAM); Enterprise Resource Planning (ERP)